KAJIAN BAHAYA EROSI PADA LAHAN KERING DI SUB DAS SAMIN KABUPATEN KARANGANYAR - Joko Winarno; Dwi Priyo Ariyanto; Retno Rosariastuti (Faculty of Agriculture, Universitas Sebelas Maret, 2008)
Title : Study of Erosion Hazard on Upland in Samin Sub Watershed, Karanganyar Regency. Samin sub watershed at Karanganyar District, Central Java has been degraded by erosion. The shed needs to be managed seriously. This research was done at Samin sub watershed at 650 – 1800 above sea level from June to November 2006. The aim of the research is studying erosion hazard on each land unit in Samin sub watershed and land management have been done farmer. This research used phenomenology qualitative description method by interpretation of theme maps and Iconos image satellite, and survey. Soil and land management sampling method was done by purposive sampling. The result of this research are land in research area very sensitive to occur land degradation because erosion hazard in light until very heavy; intercropping system in land unit 1, 2, 3, 4, 5, 6, 7, and 8 is the best method to land conservation and diversification of agriculture yield; soil management method and intercropping system have been done by farmer are the best of land conservation Keywords: Erosion, Samin Sub Watershed, upland, intercropping, soil management